2004
DOI: 10.1111/j.1741-6612.2004.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

The humble telephone: a medium for running carer support groups

Abstract: Objective: Teleconferencing is commonly used in business to conduct meetings and interviews. It can also be used to conduct education and support groups for carers who are not able to attend face‐to‐face groups. The Carer Support Network Project was funded by the New South Wales (NSW) Government to promote the use of telephone support groups for carers of people living with dementia. Method: Twenty‐two health and community workers were trained in the conduct of telephone support groups and were helped to or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Lone carers also expressed a desire to talk with others in the same situation but did not believe that this was possible. Consequently, service providers should consider using telephone support groups (Shanley et al. 2004) as a means of providing such isolated carers with peer support.…”
Section: Discussionmentioning
confidence: 99%
“…Lone carers also expressed a desire to talk with others in the same situation but did not believe that this was possible. Consequently, service providers should consider using telephone support groups (Shanley et al. 2004) as a means of providing such isolated carers with peer support.…”
Section: Discussionmentioning
confidence: 99%
“…Telephone groups have been used to provide emotional support, deliver information, assist with problem solving, share experiences, and reduce isolation among a number of different targeted clientele in the health and welfare fields and especially for those who are geographically dispersed or distant from mainstream services. These client groups include women with (Jalovcic & Pentland, 2009), older stroke caregivers (Hartke & King, 2003), caregivers of people with brain injury (Brown et al, 1999), carers of people with dementia and dependent elderly adults (Rosswurm, Larrabee, & Zhang, 2002;Shanley, 2008;Shanley, Roddy, Cruysmans, & Eisenberg, 2004;Smith & Toseland, 2006), HIV-positive persons (Meier, Galinsky, & Rounds, 1995;Nokes, Chew, & Altman, 2003), Alzheimer's disease caregivers (Martindale-Adams, Nichols, Burns, & Malone, 2002), parents of children with chronic conditions (Ritchie et al, 2000), women with breast cancer (Heiney et al, 2003), and homebound elderly (Kaslyn, 1999).…”
Section: Telephone-mediated Group Work: the Telegroup Counselling Promentioning
confidence: 99%
“…Groupwork requires a facilitator to adopt, explicitly or implicitly, a therapeutic model to guide process. Choice of framework must take into account possibly different demands in a telephone environment, with some guidelines available for developing healthy sustainable models of connections by telephone (e.g., Shanley, Roddy, Cruysmans, & Eisenberg, 2004). This includes engaging in creative ways of maintaining connection outside of telephone sessions (Regan & Barnwell, 1997).…”
Section: Interacting With Facilitatormentioning
confidence: 99%
“…Rather, if the support was sourced only to an "expert" facilitator, there is a risk participants may feel disempowered within the telephone relationship network-serving to enhance rather than ameliorate feelings of isolation. Shanley et al (2004) explored the telephone medium with isolated carers, finding it was a common experience for facilitators to worry that participants would feel uncomfortable with the technology. Despite this concern, Shulman (1992) found that facilitators were surprised at how quickly participants opened up-in particular, connecting via telephone (rather than face-to-face) was a positive in allowing a certain level of anonymity, which a number of the participants appreciated.…”
Section: Interacting With Facilitatormentioning
confidence: 99%